Exploring the use of grammatical metaphor in Indonesian EFL learners’ academic writing - Afifi, Nur (Universitas Pendidikan Indonesia, 2021)
Grammatical metaphor is considered to be the key linguistic resource in the creation of academic discourse. In a pedagogical context, identification of grammatical metaphor in students’ writing can be used as a measurement of students’ academic literacy level to determine actions to improve the existing situation. In Indonesian EFL context, students’ grammatical metaphor deployment and development has not been much studied, despite its strategic role in improving students’ academic literacy. This paper presents a first step towards understanding Indonesian tertiary students’ linguistic strengths and weaknesses in academic literacy through the identification of ideational grammatical metaphor deployment and development. Using cross-sectional data from first year and third year students in a State Islamic College in a rural area of Indonesia, the students’ academic writing were analyzed for the deployment of experiential grammatical metaphor. The findings show that the two groups of different levels of participants deployed similar types of reconstrual of experiential grammatical metaphor. Process to Thing transcategorisation was the most frequent type of experiential grammatical metaphor reconstrual across the two groups, while Relator to Process was the most frequent logical grammatical metaphor reconstrual in both groups. Third-year students surpassed the first-year group in the frequency and proportion of instances of grammatical metaphor deployment. This study has shown that the development of learners’ academic writing was limited. Thus, it was suggested that a more explicit pedagogy to expose students to grammatical metaphor and more basic lexicogrammar teaching to enable the students to write academic texts is warranted.